Corps éclatés : représenter l’Africain au muséum d’histoire naturelle de Toulouse (1875-1990) - Pierre Bourrasse (Les Cahiers de Framespa)
The museum of natural history of Toulouse was funded in 1865. It purchased ten busts made of plaster from the Museum of Paris, its national equivalent. Some of these busts were of African persons. It was usual in anthropological practice to display parts of bodies of colonial people in this way. But in Toulouse, the interest of this practice was limited, particularly in the context of the main studies on prehistory. Dr Pales’ donation in 1934 was different. The casts of different parts of African bodies are supported by racialized and colonial theories.